Comparison of Neutrofil-Lymphocyte Ratio to Severity of Stroke Ischemic Based of Vascular Territory Assessed By Ct-Scan - Stanliko, Stanliko; Tandiono, Michelle; Chiuman, Linda (Blantika: Multidisciplinary Journal, 2024)
Diagnosing severity of the stroke requires a NIHSS score which is a graded neurological examination. However, despite its successes, there are problems with the NIHSS. The scale contains items with poor reliability and has been criticized for its redundancy and complexity may not capture the full range of stroke severity, particularly in those with very mild or severe symptoms. Over the last 10 years, the evaluation of the NLR as an emerging marker of diseases has become a compelling field of bio-medical research. However, the value of NLR in predicting the poor prognosis of stroke patients is still controversial. Patients of stroke ischemic from July to December 2023 at Royal Prima Hospital were studied to analyze the correlation between NLR to severity of stroke regarding vascular territory. Our investigation reveals no correlation between those two variablesation between those two variables.